Prospects and Perspective of Essential Oil-Bearing Plants: A Case Study of Lemongrass Cultivation in Fallow Land and Chemoprospecting of Essential Oil - Kumar, Vineet; Bhattarai, Sushil; Chauhan, Preeti; Guleria, Rishika; Sharma, Pradeep (Indian Forester, 2022)
India has vast uncultivated areas such as marginalized lands, barren lands, unused land spaces, wastelands, side bunds, and areas having menace of wild/grazing animals. Surprisingly, the uncultivated area is progressively increasing due to various factors. Nevertheless, the unused lands can be utilized for beneficial purposes. Therefore, a case study was undertaken to cultivate lemongrass in uncultivated land and the cost-benefit analysis indicated that it could be a source of decent livelihood generation and an additional income source for village communities. Further, simple steps of essential oil isolation and its fractionation to isolate fine chemicals and enriched fractions, and inclusive utilization of the leftover biomass are extremely useful for enterprise development and employment generation in the hilly and rural areas. Apart from tangible benefits, the approach is also useful for reclamation of uncultivated lands, mitigation of climate change, soil health improvement, reducing the menace of invasive species, and in line with sustainable development goals to achieve a better future for all. The case study could be a model to benefit each member of society and improve the overall economy and environment.